STRATEGI GURU DALAM MENGATASI BULLYING DI LINGKUNGAN SEKOLAH DASAR - Annisa Fardiyatul Muslimah; Muslim; Budianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Bullying is a phenomenon that often occurs in the world of education, including the elementary school environment. So that to prevent and handle it requires the right strategy. This study aims to identify factors that influence bullying behavior and explain the strategies used by teachers in overcoming bullying behavior that occurs in the elementary school environment. This study was conducted in one of the elementary schools in Karawang Regency. This research used a qualitative approach with a case study method. Data collection techniques included interviews with four homeroom teachers, observation, and documentation taken during the study. The results showed that the factors that influence bullying behavior in elementary schools include individual factors, peers, and social media. Teachers' strategies in overcoming bullying include prevention and treatment strategies. The prevention strategies used are instilling character education through reading the Qur'an and praying duha, providing classical guidance, collaborating with parents, monitoring students who often bully and creating study groups. The handling strategies used by teachers are providing classical guidance in front of the class, finding out the root of the problem first, giving appeals as well as warnings to bullying perpetrators, imposing punishment on bullying perpetrators, communicating with parents to inform the problems experienced by children when in the school environment, and involving parents in the reconciliation process between students involved in bullying actions.